(untitled) (Ustozlar uchun, 2026)
Bus stop dwell time is one of the main operational factors affecting the regularity of urban bus services. Even when route length, fleet size, and timetable structure are acceptable, irregular operation can emerge because of excessive boarding and alighting time at critical stops. This paper develops an improved mathematical model for assessing the influence of dwell time at bus stops on urban bus service regularity. The proposed approach combines a stop-level dwell time function with a route-level regularity equation. The stop-level function includes passenger boarding, passenger alighting, and stop crowding effects, while the route-level model links cumulative dwell time to the regularity coefficient. A computational experiment was carried out for a model urban route with several demand scenarios. The results showed that an increase in cumulative dwell time from 2,1 minutes to 5,1 minutes reduced the expected regularity level from 88,8% to 74,8%. The estimated regularity model indicates that each additional minute of cumulative dwell time decreases regularity by 4,68 percentage points. The proposed model can be used in timetable revision, stop-level diagnostics, dispatch control, and route improvement planning.